The effects of the invasive mussel mytilus galloprovincialis and human exploitation on the indigenous mussel Perna perna on the South Coast of South Africa - Rius Viladomiu, Marc (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
In South Africa, the indigenous mussel Perna perna is threatened by both an invasive species and excessive human exploitation. The Mediterranean mussel Mytilus galloprovincialis is an invasive species that has been introduced to many parts of the world. In South Africa, this species arrived in the 1970s and spread rapidly along the west coast where today it is the dominant mussel species. Along the west coast, M. galloprovincialis is competitively superior in all aspects to the indigenous mussel species, and, as a result, has displaced some of them. On the south coast, M. galloprovincialis found more oligotrophic waters, higher species richness, and a stronger competitor in the indigenous mussel P. perna. The rate of spread of M. galloprovincialis along the south coast has decreased over the last 10 years and the present eastern limit of its distribution in South African is East London. On the south coast, M. galloprovincialis has not yet completely replaced P. perna; instead, the two exhibit spatial segregation, with P. perna dominating the low shore, M. galloprovincialis the high shore and an overlap zone between the two. An experiment on competition was carried out at one site on the south coast. The results showed that, on the low shore, P. perna is a more dominant competitor for space than M. galloprovincialis. Also byssus attachment of the two species differs, P. perna being much stronger than M. galloprovincialis, which suffers high mortality due to wave action on the low shore, especially in monospecific beds. As a result, mortality of M. galloprovincialis through wave action is reduced by the presence of P. perna, which seems to confer protection against dislodgement. However, in the absence of strong wave action, P. perna competitively excludes M. galloprovincialis. Human exploitation along 160 km of coast was examined by sampling mussel populations and using aerial surveys to determine where harvesters were distributed. Collectors did not seem to discriminate between species. The study has shown that higher abundances of mussels were found in protected or inaccessible sites, while in unprotected sites mussels were scarce. Coastal nature reserves are being proven to be effective in protecting mussel populations.
Keywords: Mussels -- South Africa; Perna -- South Africa; Mytilus galloprovincialis -- South Africa; Mytilidae -- South Africa; Biological invasions; Marine resources conservation -- South Africa